2021
DOI: 10.1007/s00392-021-01873-4
|View full text |Cite
|
Sign up to set email alerts
|

Large extracellular vesicles in the left atrial appendage in patients with atrial fibrillation—the missing link?

Abstract: Atrial fibrillation (AF) is the most frequent arrhythmic disease in humans, which leads to thrombus formation in the left atrial appendage and stroke through peripheral embolization. Depending on their origin, large extracellular vesicles (lEVs) can exert pro-coagulant functions. In the present study, we investigated how different types of AF influence the levels of large EV subtypes in three distinct atrial localizations. Blood samples were collected from the right and left atrium and the left atrial appendag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In this context, the main cause of stroke in the general population has been described to be the embolization of the thrombus typically formed in the left atrial appendage in the context of AF ( 60 ). The relationship between AF, EVs, miRNAs, and the risk of stroke has recently been tested by Zietzer et al ( 61 ). These authors characterized cell-derived EVs (endothelial cells, platelets, and erythrocytes) isolated from the left atrial appendage of patients with permanent AF, non-permanent AF, and no history of AF.…”
Section: Circulating Mirnas and Risk For Mace In Afmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the main cause of stroke in the general population has been described to be the embolization of the thrombus typically formed in the left atrial appendage in the context of AF ( 60 ). The relationship between AF, EVs, miRNAs, and the risk of stroke has recently been tested by Zietzer et al ( 61 ). These authors characterized cell-derived EVs (endothelial cells, platelets, and erythrocytes) isolated from the left atrial appendage of patients with permanent AF, non-permanent AF, and no history of AF.…”
Section: Circulating Mirnas and Risk For Mace In Afmentioning
confidence: 99%
“…non-permanent AF. Based on in vitro experiments, these authors suggested that, in a state of platelet activation, platelet-derived EVs loaded with miR-223 transfer this miRNA to endothelial cells, thereby reducing endothelial healing ( 61 ), a key process to control thrombosis ( 62 ). These data therefore suggest for the first time a role for EVs loaded with miRNAs as a thrombogenic mechanism in AF.…”
Section: Circulating Mirnas and Risk For Mace In Afmentioning
confidence: 99%
“…Zietzer et al proved that patients suffering from AF had higher levels of large EVs derived from platelets in the left atrial appendage than patients with no AF. Moreover, patients with permanent AF presented higher levels of these EVs when compared with non-permanent AF patients [ 61 ]. All studies discussed in this subsection with additional data are summarized in Table 4 .…”
Section: Extracellular Vesicles In Patients With Atrial Fibrillationmentioning
confidence: 99%
“…Atrial fibrilation (AF) is the most common type of cardiac arrhythmias, which is characterised by irregular rhythm and can result in a reduction of cardiac output and may lead to thrombus formation and consequently to potentially fatal strokes. 1 Risk factors of AF include heart failure, obesity, diabetes, hypertension, and aging. Development of AF has been correlated with increased arterial stiffness and is more prevalent in aging adults.…”
Section: Introductionmentioning
confidence: 99%